Psychometric properties of the Slovak translation of the NEO-PI-R questionnaire - Lisà, Elena; Kohút, Milan (Ricerche di Psicologia - Open Access, 2022)
The study aimed to verify the psychometric properties of the NEO-PI-R Slovak translation. The self-report sample consisted of 1.062, a retested sample of 122, and an observer rater of 371 persons. In self-assessments, Cronbachʼs alfa of domains ranged from .88 (Openness) to .92 (Neuroticism). In observer ratings, the reliability ranged from .89 (Extraversion) to .95 (Conscientiousness). The stability of the test-retest showed an average correlation of r = .81 after three months. Exploratory factor analysis revealed five factors that explained the variance of 60.45%. The agreement between the observers and the self-assessments was at a mean level of .58. The Slovak translation of NEO-PI-R follows the psychometric standards for reliability and construct validity. The study did not follow the educational level and mental health of the research participants.